Endoscopic Ultrasound-Guided Vascular Procedures: A Review - Dominic A. Staudenmann; Arthur J. Kaffes; Payal Saxena (Clinical Endoscopy, 2020)
Since the 1980s, endoscopic ultrasound has advanced from being purely diagnostic to an interventional modality. The gastrointestinal tract offers an exceptional window for assessing the vascular structures in the mediastinum and in the abdomen. This has led to a rapidly growing interest in endoscopic ultrasound-controlled vascular interventions as a minimally invasive alternative to surgical and radiological procedures.